Ankylosing Spondylitis: Review of Clinical Features, Diagnosis, and Treatment - Szymon Markowiak; Marta Wardęszkiewicz; Wiktoria Jabłońska; Amelia Kasprzak; Maciej Świercz; Monika Truchta; Aleksandra Mańkowska; Agata Kolano; Anna Pejas (Kazimierz Wielki University, 2024)
Introduction Ankylosing spondylitis (AS) is a chronic inflammatory disorder affecting the spine and joints, leading to significant physical impairment. With a prevalence of 0.1-1.4%, AS holds significance in healthcare and socioeconomic contexts, therefore a thorough understanding is crucial for diagnosis and effective management. This article provides a current state of knowledge of the subject for clinicians and patients.   Review methods English-language scientific literature found in PubMed, Web of Science, Google Scholar and Wiley databases (2015-2023) was used for the review. Articles were searched based on keywords. Each article was analysed for knowledge currency and relevance for use in the review.   Description of the State of Knowledge After searching the articles, 20 articles were selected for final analysis. The data collected provides the latest information on ankylosing spondylitis. The etiology of AS has a strong association with the HLA-B27 antigen and research is being conducted on the association with HLA-15, IL-1, IL-23R, ERAP-1 and ERAP-2. Clinical manifestations include a broad spectrum of symptoms involving the musculoskeletal, ocular, respiratory, cardiovascular, gastrointestinal and psychiatric systems. Specific diagnostic guidelines have been published by ASAS and EULAR. Treatment includes NSAID, GCS and biologic drug therapy.   Summary AS, with its complex etiology and diverse clinical manifestations, presents a diagnostic challenge to clinicians. The variable prognosis and complex treatment in AS requires physicians to continually update their knowledge. Early diagnosis and treatment initiation can improve the patient's prognosis.